Novas An??lises da T??cnica SHARP(Spectrum Harvesting with ARQ Retransmission and Probing) em R??dio Cognitivo - Rocha , N??colas Wilson Ribeiro (2021)
Cognitive radio consists in a new technology that searches for available channels and allows new transmissions opportunities for coexisting users, optimizing the spectrum usage and increasing wireless communications efficiency. This work proposes additional analysis and extensions of the method entitled Spectrum Harvesting with ARQ Retransmission and Probing (SHARP), a cognitive radio network technique in which primary and secondary users coexist. The secondary pair listens to the primary receptor Automatic Repeat Request (ARQ) feedback in order to glean information about the primary channel and probe it, getting additional data of the direct and cross channel gains. This probing mechanism and two varieties of spectrum sharing, named conservative and aggressive SHARP, are used depending on the desired secondary user interference in the primary. The study focuses in two main aspects: allowing more retransmission possibilities in the original system and observing the delay effects in the model. New operating regions and their probabilities are derived. The transmissions throughput and the system delay are calculated. Numerical results shows the influence in the system performance by increasing the number of retransmissions and the importance of considering the delay in its analysis.